Atlas of unknowable things - Templeman, McCormick (St. Martin's Press, 2025)
"The Seven Husbands of Evelyn Hugo meets Modern Gothic in this smart and upmarket horror novel. Atlas of Unknowable Things begins when a young college professor writing on the occult joins an isolated research think-tank on a sprawling estate high in the Rocky Mountains. Her colleagues are a group of stand-offish fellows and the estate full of references to the occult. She slowly becomes plagued by nightmares and bouts of sleeping walking when she discovers a previous attendee had mysteriously disappeared - who seems to be leaving her clues on the true purpose for the research center. As she delves deeper into the mystery the more she becomes confused and questions reality. It's only after she discovers her personal connection to the facility, and the real reason why the former researcher left, that the true monstrous horror of the research center is unleashed...literally"-- Provided by publisher.